Hemodynamic Instability and Severity Grade of Kidney Trauma as The Predictor Factors for Nephrectomy - Besut Daryanto; I Gusti Lanang Andi Suharibawa; Kurnia Penta Seputra; Paksi Satyagraha; Pradana Nurhadi (Brawijaya Journal of Urology, 2020)
Introduction: Kidney trauma occurs in presumably 1-5% of all trauma cases. Delayed surgery increases the likelihood of persistent urinary extravasation and secondary hemorrhage, whereas immediate surgery results in a high renal loss. Hence, the aims sought to evaluate whether hemodynamic instability, urea and creatinine level, anemia and severity grading of kidney trauma can be the predictor factors of nephrectomy. Materials and Methods: Retrospectively study from January 2005 to December 2016, the authors collected the data of 63 kidney trauma patients. We analyzed the hemodynamic condition, hemoglobin level, and grade of kidney injury. The association of hemodynamic instability, urea and creatinine level, anemia, grade of kidney injury to the decision of nephrectomy were analyzed using statistical software (SPSS). Results: Kidney trauma occurred mostly in first grade (40/63.5%). Only 4 (5.4%) came in high grade of renal trauma (Grade III and IV). Patients who came to the emergency department mostly in stable hemodynamic (52/82.5%). Most of them were subsequently treated uneventfully with non-operative management (60/95.2%). There was a significant association between hemodynamic instability and treatment options that unstable hemodynamic significantly increase nephrectomy rate (p=0.047). The data analysis results associated severe grade of trauma with an increase nephrectomy rate (RR: 174, 95% CI:8.62 – 315.174, p<0.01). Further, there were no significant association between anemia, urea and creatinine levels to nephrectomy rate (p>0.05). Conclusion: Severity grade of kidney trauma and hemodynamic instability increased the risk of nephrectomy. Other factors such as anemia, urea and creatinine levels do not have a significant association with the risk of nephrectomy.